Sex-specific differences in pre-stroke characteristics reveal vulnerability of elderly women - Hoyer, Carolin; Schlenker, Jan; Sandikci, Vesile; Ebert, Anne; Wittayer, Matthias Sebastian; Platten, Michael; Szabo, Kristina (Journal of Personalized Medicine, 2022)
While the sexually dimorphic character of ischemic stroke has been acknowledged along several dimensions, age-specific sex disparities regarding pre-stroke characteristics in particular have received comparatively little attention. This study aimed to identify age-dependent associations between sex and risk factors, premorbidity, and living situation in patients with ischemic stroke to foster the continuing development of dedicated preventative strategies. In a retrospective single-center study, data of patients with acute ischemic stroke (AIS) admitted to the Department of Neurology, University Hospital Mannheim, Germany, between June 2004-June 2020 were included; AIS frequency, vascular risk factors, premorbidity, living situation, and stroke etiology were analyzed across sexes and different age spectra. From a total of 11,003 patients included in the study, 44.1% were female. Women aged >70-≤90 years showed a pronounced increase in stroke frequency, lived alone significantly more frequently, and had a significantly higher degree of pre-stroke disability than men; however, only hypertension and atrial fibrillation were more prevalent in women in this age segment. The seventh and eighth decades are a critical time in which the pre-stroke risk profile changes resulting in an increase in stroke morbidity in women. This emphasizes the relevance of and need for an approach to stroke prevention that is both targeted and integrative.
Gesehen am 23.04.2024